Business intelligence serious game participatory development: lessons from ERPsim for big data. Issue 3 (5th June 2017) - Labonte-LeMoyne, Elise; Leger, Pierre-Majorique; Robert, Jacques; Babin, Gilbert; Charland, Patrick; Michon, Jean-François
Abstract : Purpose: A major trend in enterprise resource planning software (ERP) is to embed business analytics tools within user-centered roles in enterprise software. This integration allows business users to get better and faster insight to action. As a consequence, it is imperative for business students to learn how to use these new tools to adequately prepare them for new expectations in the industry. The paper aims to discuss these issues. Design/methodology/approach: In this paper, the authors propose a new serious game, called ERPsim for big data, to enable the learner to acquire abilities at each level of the business analytics learning taxonomy. To maximize the pedagogical impact of the game, participatory design (PD) with professors as co-designers was used during game development. Findings: This case study presents the PD approach and analyses the efficacy of the proposed new simulation. Originality/value: The authors conclude by providing recommendations and lessons learned from this approach.